Research progress in preparation technology of SiCf/SiC ceramic matrix composites - WANG Yanfei; LIU Rongjun; ZHANG Jin; DU Jinping; LI Duan (Cailiao gongcheng)
Continuous silicon carbide fiber reinforced silicon carbide （SiCf/SiC） ceramic matrix composites are considered as the most promising advanced materials in the fields of hot end components of aviation turbine engines and thermal protection structures of novel aerospace aircraft due to their excellent comprehensive properties， such as light weight， high strength and toughness， high temperature resistance， and oxidation resistance. In this paper， the preparation technology of the four elementary components of SiCf/SiC composites， such as SiC fiber， interphase， SiC matrix，and environmental barrier coating （EBC）， has been systematically reviewed， and the bottleneck problems of SiCf/SiC composites in the future development have been proposed. The current third-generation SiC fibers possess a near stoichiometric C/Si ratio and have excellent high temperature stability and mechanical properties. The structure and oxidation resistance of interphase plays a decisive role in the mechanical properties of SiCf/SiC composites in harsh service environments. The research frontiers are to develop novel interphases that matches SiC fiber and has excellent oxidation resistance，achieving continuous and uniform preparations of such interphases. PIP， CVI and RMI techniques are commonly employed to prepare SiCf/SiC composites， but a single technique no longer meets the performance requirements of the composite. Hence， a hybrid technique such as the hybrid CVI-PIP technique has been employed to manufacture SiCf/SiC composites， through which processing parameters， microstructures， and mechanical properties have been widely investigated. Environmental barrier coatings are used as a barrier to prevent SiCf/SiC composites from corrosion and degradation by external corrosive environments. Based on the third generation Si/Yb2Si2O7 EBC system， highly reliable and long life-span environmental barrier coatings can be prepared by supplementing Si sources and self-healing cracks， thereby greatly improving the service life of SiCf/SiC composites components. To achieve a wider application of SiCf/SiC composites， further research work should be carried out in areas such as the structural design of composite components， low-cost manufacturing， development of new anti-oxidation interphases， development of novel EBCs with anti-peeling off and anti-cracking natures， failure analysis and life prediction of composite.